Association Between the History of Fall and the Fear of Falling on Stair Descent and Gait Transition Spatiotemporal Parameters and Lower-Limb Kinematics in Older Adults - Ivone Teles; Juliana Moreira; Andreia S. P. Sousa (Applied Sciences, 2025)
Background: Among older adults, there is a high incidence of history of fall (HoF), fear of falling (FoF), and falls on stair descent during gait transitions. Purpose: We aim to evaluate the association between HoF and FoF on spatiotemporal and lower-limb kinematic parameters in older adults during stair descents and gait transitions. Methods: Sixty older adults (>60 years) were evaluated through an optoelectrical motion capture system during stair descents and gait transitions, using the mean value of the task velocity and time; single- and double-support time; peak downward center of mass (CoM) velocity; hip, knee, and ankle positions of ipsi and the contralateral limb; and foot clearance and foot placement, assessed through multivariate analysis of variance. Results: FOF exhibited longer time to complete (p = 0.009) and double-support (p = 0.047) and single-support (p = 0.009) times and a reduced peak downward CoM velocity (p = 0.043). In the gait transition cycle, HOF exhibited reduced ipsi ankle angles at toe-off (p = 0.015), and FOF presented reduced ipsi ankle angles at heel-strike (p = 0.041) and toe-off (p = 0.026) and reduced contralateral ankle angles at toe-off (p = 0.022). Conclusion: Older adults with HoF and FoF exhibit biomechanical changes during stair descents and gait transitions, in line with the use of more conservative strategies to avoid falling.